The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0893-133x(01)00420-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilateral 6-Hydroxydopamine Lesions of the Medial Forebrain Bundle on Reaction Time

Abstract: Overt symptoms of Parkinson's disease do not manifest themselves until there is a substantial loss of the dopaminergic nigrostriatal projection. However, as neuroprotective strategies are developed, it will be essential to detect the disease in its preclinical phase. Performance on conditioned reaction time tasks is known to be impaired by extensive 6-hydroxydopamine-induced lesions of theThe primary neuropathology of Parkinson's disease is the loss of dopamine (DA) neurons within the substantia nigra (SN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Similar perseverative behavior has often been associated with response deficits observed in animals with lateral striatum excitotoxic or 6-OHDA lesions (Kirkby, 1969;Amalric et al, 1995;Devan et al, 1996;Eagle et al, 1999;El Massioui et al, 2001;Smith et al, 2002) and was interpreted as either an inability to inhibit ongoing actions or as a failure to initiate a new response. Moreover, the lack of response latency impairment could be attributable to the extent of our striatal DA depletion, because 6-OHDA infusion in the medial forebrain bundle that induces similar DA depletion produces no reliable impairment in a reaction time task (Smith et al, 2002) or skilled paw use (Przedborski et al, 1995;Lee et al, 1996). Significant impairment in skilled paw reaching does not appear unless 80 -90% of striatal TH-positive fibers density or 60 -80% of TH-positive neurons in substantia nigra are lost (Barneoud et al, 1991;Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 73%
“…Similar perseverative behavior has often been associated with response deficits observed in animals with lateral striatum excitotoxic or 6-OHDA lesions (Kirkby, 1969;Amalric et al, 1995;Devan et al, 1996;Eagle et al, 1999;El Massioui et al, 2001;Smith et al, 2002) and was interpreted as either an inability to inhibit ongoing actions or as a failure to initiate a new response. Moreover, the lack of response latency impairment could be attributable to the extent of our striatal DA depletion, because 6-OHDA infusion in the medial forebrain bundle that induces similar DA depletion produces no reliable impairment in a reaction time task (Smith et al, 2002) or skilled paw use (Przedborski et al, 1995;Lee et al, 1996). Significant impairment in skilled paw reaching does not appear unless 80 -90% of striatal TH-positive fibers density or 60 -80% of TH-positive neurons in substantia nigra are lost (Barneoud et al, 1991;Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 73%
“…Smith et al (2002) showed that maximum degeneration of striatal DA is observed between day 5 and 7 days post-intracerebral injection of 6-OHDA into the medial forebrain bundle. Therefore, oleanolic acid could not exert its beneficial effects and provide neuroprotection in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Following these procedures the experimental contingencies were reversed such that all rats had to turn in the untrained direction. After the reversal, the contralaterally lesioned group had to turn toward the lesion and consequently easily acquired the reversal, however, reinforced rates of responding did not reach preoperative rates possibly due to altered motivation (Mogenson et al, 1980; Smith et al, 2002; Wise, 2002; Solstad et al, 2008). Conversely, the ipsilaterally lesioned group had to turn away from the lesion and consequently was unable to acquire the reversal and continued to turn in the originally trained direction (Szostak et al, 1988).…”
Section: The Influence Of Animal Training On Da Imbalance In the Nigrmentioning
confidence: 99%